Lógica dialética e crítica à razão instrumental: a Teoria Crítica de Max Horkheimer - Deivisson Oliveira Silva (2015)
This dissertation analyses the philosophical works of Max Horkheimer produced on two distinct moments: the 1930s and 1940s. In this first stage, the present work investigates Horkheimers objective on elaborating a materialist dialectical logic on close cooperation with social research, during the moment when his first critical model is developed. Afterwards, it is examined the philosophy developed by Horkheimer on collaboration with Theodor W. Adorno which consolidated as a critique of instrumental rationality. On this second moment it is also examined the interweaving of reason and domination and the resulting difficulties for the possibility of the critique, in the scope of the Dialectic of Enlightenment. Lastly, this work investigates Horkheimers book the Eclipse of Reason which develop a critique to rationality from the dialectical mediation between subjective and objective reason.